Educator and Student Interaction in a Classroom Learning Atmosphere - Ode Yahyu Herliany Yusuf; Feni Aprianti; Dian Mayasari; Satriwati Satriwati; Waode Erma Balula (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The pattern of interaction between educators and students cannot be separated from the world of education, educators are the main factor in the success of an effective and efficient class. Effective learning can be done by creating student motivation to always be involved and participate in the learning process in class. In order to create an effective learning atmosphere, namely by creating a sense of comfort, fun and motivation so that it becomes a driving force and encouragement for student learning. Therefore success in the learning process of students must be supported by competent teachers.